Inhibited transcription factor EB function induces reactive oxygen species overproduction to promote pyroptosis in cadmium-exposed renal tubular epithelial cells. (1st December 2022) - Dong, Peng-Fei; Li, Zi-Fa; Lian, Cai-Yu; Wang, Zhen-Yong; Wang, Lin
Abstract: Pyroptosis is a pro-inflammatory type of cell death involved in the pathogenesis of multiple kidney diseases, while transcription factor EB (TFEB) is shown to be important for rescuing renal function. Cadmium (Cd) is an omnipresent toxic heavy metal with definite nephrotoxicity, but there is lacking of evidence regarding an interplay between TFEB activity and pyroptosis during Cd exposure. In this study, Cd-exposed NRK-52E cells were used to clarify this issue as an in vitro model of acute kidney injury. First, our results showed that Cd exposure evidently elevated the protein levels involved in pyroptosis, increased lactate dehydrogenase (LDH) release, and disrupted the cell membrane integrity, suggesting the occurrence of pyroptosis in NRK-52E cells. It is also shown that Cd induced a burst of reactive oxygen species (ROS) to mediate pyroptosis. Simultaneously, downregulated TFEB expression with its inhibited nuclear translocation was revealed in Cd-exposed NRK-52E cells. Further investigations have demonstrated that TFEB knockdown promoted Cd-induced ROS production to exacerbate the pyroptosis, while TFEB overexpression inhibited Cd-induced ROS production to alleviate the pyroptosis in NRK-52E cells. In summary, these findings demonstrate that Cd-inhibited TFEB function results in ROS overproduction to promote pyroptosis in NRK-52E cells, which provide new insight into the therapeutic targets for Cd-induced kidney diseases. Graphical abstract: Image 1 Highlights: Cadmium (Cd) exposure can cause pyroptosis in renal tubular epithelial cells. Cd-induced pyroptosis results from reactive oxygen species (ROS) overproduction. Cd-inhibited transcription factor EB (TFEB) function causes ROS overproduction. Inhibited TFEB function contributes to pyroptosis during Cd exposure.